2023
DOI: 10.3390/wevj14080230
|View full text |Cite
|
Sign up to set email alerts
|

Aligned Simulation Models for Simulating Africa’s Electric Minibus Taxis

Chris Joseph Abraham,
Arnold Rix,
Marthinus Johannes Booysen

Abstract: Planning for the eventual electrification of transport in sub-Saharan Africa requires accurate simulation of its unique transport systems. The few studies that attempt to model electric minibus taxis—vehicles extensively used in sub-Saharan Africa’s public transport systems—vary greatly in their results. This paper analyses, compares and corrects the only two existing studies that project energy consumption of electric minibus taxis in the region. One of the studies projected an energy consumption of 0.39 kWh/… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…However, as energy efficiency is driving style dependent, an efficiency representative of the South African minibus industry is needed for this paper. One such study has found an energy efficiency of 0.55 kWh/km, which will be used in this paper [64].…”
Section: Vehicle Datamentioning
confidence: 99%
“…However, as energy efficiency is driving style dependent, an efficiency representative of the South African minibus industry is needed for this paper. One such study has found an energy efficiency of 0.55 kWh/km, which will be used in this paper [64].…”
Section: Vehicle Datamentioning
confidence: 99%
“…From the flow diagrams, the two main models used in Figure 8 are the electric motor model, indicated on the diagrams as 'EM-model', which refers to the powertrain efficiency model built by Lacock et al [7], and the 'Electro-kinetic EV model', which refers to the simulation developed by Abraham et al [37], in which the propulsion efficiency, η prop , was assumed to be constant.…”
Section: Simulationmentioning
confidence: 99%
“…These parameters are only suggestions and are fully modifiable to the user if they wish to use other EVs as a reference. If the user only wishes to modify the battery capacity, it is suggested that the energy efficiency is modified according to the suggested ratios by Abraham et al [39]. In the extended version of Grid-Sim, users have the option to include external batteries and a solar charging station.…”
Section: Scenario Initialisationmentioning
confidence: 99%